Quantitative analysis and characterization of floral volatiles, and the role of active compounds on the behavior of Heortia vitessoides - Qian, Chenyu; Xie, Wenqi; Su, Zhongqi; Wen, Xiujun; Ma, Tao (Frontiers in Plant Science, 2024)
This study explores the role of floral volatile organic compounds (FVOCs) in insect behavior, focusing on Aquilaria sinensis (AS), a valuable tropical plant threatened by Heortia vitessoides Moore. Despite H. vitessoides' attraction to AS and non-host plants like Elaeocarpus decipiens (ED) and Dalbergia odorifera (DO), little is known about their chemical interactions. FVOCs from these plants were analyzed at 9:00 and 18:00 using GC×GC-QTOF-MS and HS-SPME. The results showed that ED exhibiting the highest concentration (92.340 ng/mg), followed by DO (75.167 ng/mg) and AS (64.450 ng/mg). Through GC-EAD and EAG, a total of 11 FVOC compounds with electrophysiological activates were identified. These compounds, except linalool, showed dose-dependent responses. Y-Tube bioassays confirmed phenylethyl alcohol or the mixture of EAD-active compounds produced positive chemotactic responses in both males and females. FVOCs have the potential to be used as a natural and sustainable alternative to chemical insecticides in pest control.